Correlation of SARS-CoV-2 Serology and Clinical Phenotype Amongst Hospitalised Children in a Tertiary Children's Hospital in India. (9th March 2021) - Venkataraman, Aishwarya; Balasubramanian, S; Putilibai, Sulochana; Lakshan Raj, S; Amperayani, Sumanth; Senthilnathan, S; Manoharan, Anand; Sophi, Arokia; Amutha, R; Sadasivam, Kalaimaran; Goenka, Anu; Ramanan, A V
Abstract: Introduction: Children usually present with minimal or no symptoms of COVID-19 infection. Antibody responses to SARS-CoV-2 in children from low- and middle-income countries (LMIC) have not been well described. We describe the prevalence of anti-SARS-CoV-2 antibodies and clinical phenotype of seropositive children admitted to a tertiary children's hospital in South India. Methods: To determine the seropositivity and describe the clinical characteristics of COVID-19 infection amongst hospitalised children, we performed a prospective clinical data collection and blood sampling of children admitted to Kanchi Kamakoti CHILDS Trust Hospital, Chennai, India over 4 months of the COVID-19 pandemic. In seropositive children, we compared antibody titres between children with and without PIMS-TS. Results: Of 463 children, 91 (19.6%) were seropositive. The median (range) age of seropositive children was 5 years (1 month–17 years). Clinical presentation was consistent with Paediatric inflammatory multisystem syndrome associated or related with SARS-CoV-2 infection (PIMS-TS) in 48% (44/91) of seropositive children. The median (range) antibody titre was 54.8 (11.1–170.9) AU/ml among all seropositive children. The median antibody titre among the children with PIMS-TS (60.3 AU/mL) was significantly ( p  = 0.01) higher when compared to the children without PIMS-TS (54.8 AU/mL). Conclusion: We describe the antibody responses to SARS-CoV-2 amongst hospitalised children in a LMIC tertiary children's hospital. Almost half of the seropositive children had PIMS-TS. Antibody levels may be helpful in the diagnosis and disease stratification of PIMS-TS. LAY SUMMARY: Children usually present with minimal or no symptoms of COVID-19 infection. However, Multisystem Inflammatory Syndrome in Children (MIS-C) or Paediatric inflammatory multisystem syndrome associated or related with SARS-CoV-2 infection (PIMS-TS) has emerged as a distinctive paediatric illness related to SARS-CoV-2. Recently, antibody testing for SARS-CoV-2 is being used increasingly as a diagnostic test for PIMS-TS. However, data on the antibody responses to SARS-CoV-2 in children are sparse. We, therefore, attempted to identify the seropositivity and describe the clinical spectrum of COVID-19 infection amongst infants and children getting hospitalised in a children's hospital in south India. Nearly one-fifth of the hospitalised children tested serology positive over 4 months. Antibody levels in children with PIMS-TS were significantly higher in comparison to the other two groups (acute COVID-19 infection and children without PIMS-TS). Results from our study suggest that all children are at risk of COVID-19 infection though they may present with mild illness or no symptoms. We also observed that antibody testing may have a possible role in diagnosis of PIMS-TS.